THE DESIGN OF STORY BOOK OF RATU KALINYAMAT LEGEND - Ratnasari, Yasinta Ayu; Gunadi, Gunadi (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2021)
The aim of this study project is to produce a draft picture book telling the story of the legend of Ratu Kalinyamat in order to preserve the wisdom of Jepara’s local culture. The work process in making this work goes through three processes, namely pre-production, production, and post- production. The process of illustration design was using manual techniques at the stage of sketching and coloring using poster paint. Then at the layout and editing stage using digital techniques with Adobe Photoshop CS6 and Adobe Illustrator CS6 software. The design of the picture book tells the story of the legend of Ratu Kalinyamat which produces thirty-two pages for story illustrations and narrative text, front cover pages, back cover pages, and supporting pages which include sub covers, character introductions, moral message pages, and author bio. The work of this study project is expected to increase children's enthusiasm in getting to know the legendary story of Ratu Kalinyamat.